PENGARUH PERSEPSI PROFESI GURU DAN LINGKUNGAN KELUARGA TERHADAP MINAT MAHASISWA MENJADI GURU DENGAN SELF EFFICACY SEBAGAI VARIABEL INTERVENING - Saniyatul Hidayah; Ruri Nurul Aeni Wulandari (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
Interest on the teaching profession is the beginning of someone’s interest to become a teacher. The research in this article is designed to measure the impact of perceptions of the teaching profession, family environment, and self-efficacy on the students’ interest to become a teacher, perceptions of the profession and family environment on self-efficacy, and the perceptions of the teaching profession and family environment on the students’ interest to become a teacher through self-efficacy. The research was conducted on 158 students in the year of 2017 and 2018 at the Administration Education Study Program of Universitas Negeri Surabaya. The research uses a quantitative method, with survey techniques. Data collection techniques using questionnaires and analyzed by path analysis. The conclusion showed that the perception of the teaching profession with a P-Value was 0.088, family environment with a P-Value was 0.000, and self-efficacy toward the students’ interest in becoming a teacher with a P-Value was 0.000. Perceptions of the profession and family environment to self-efficacy with a P-Value were 0.000 and 0.004. Perceptions of the teachingprofession and family environment to students’ interest in becoming a teacher through self-efficacy with a P-Value were 0.003 and 0.011. Hence, it could be concluded that H1 was rejected and H2, H3, H4, H5, H6, and H7 were accepted in this research.